2021
DOI: 10.1002/14651858.cd013170.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cough augmentation techniques for people with chronic neuromuscular disorders

Abstract: Analysis 3.1. Comparison 3: Mechanical insu lation-exsu lation (MI-E) versus mechanical insu lation (MI) plus manually assisted cough (MAC), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Both absolute and standardized LFTs were measured and reported according to the European Respiratory Society Guidelines and the Global Lung Function Initiative. 30 Although a recent Cochrane review suggested that Peak Cough Flow (PCF) improves after a range of cough augmenting techniques compared to unassisted cough, 31 we decided not to use this as an outcome parameter. Measurement of PCF requires an additional maneuver which may result in fatigue with negative impact on LFT results.…”
Section: Methodsmentioning
confidence: 99%
“…Both absolute and standardized LFTs were measured and reported according to the European Respiratory Society Guidelines and the Global Lung Function Initiative. 30 Although a recent Cochrane review suggested that Peak Cough Flow (PCF) improves after a range of cough augmenting techniques compared to unassisted cough, 31 we decided not to use this as an outcome parameter. Measurement of PCF requires an additional maneuver which may result in fatigue with negative impact on LFT results.…”
Section: Methodsmentioning
confidence: 99%
“…Although a previous study that investigated the use of MI-E in healthy Landrace-Large White female pigs showed that +40/-70 cmH 2 O was the most effective pressure combination [ 17 ], MI-E settings with a pressure of ±40 cmH 2 O are most commonly used in invasively ventilated critically ill patients [ 18 ]. Previous studies demonstrated the safety of MI-E; [ 19 , 20 ] however, conflicting findings have been reported [ 21 ]. Since another study demonstrated that pressures of ±54 cmH 2 O were tolerated well [ 10 ], we assumed that a pressure of ±40 cmH 2 O may also be tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…However, daily versus continuous rental costs and the accessibility to MI-E should be taken into account when prescribing the device. As a preventive measure, the optimal frequency of MI-E use remains unknown [45]. Furthermore, on an individual level, the need for airway clearance may change with disease progression and added morbidities [35].…”
Section: Discussionmentioning
confidence: 99%